Good in Providing Oral Care, but we Could be Better—Nursing Staff Identification of Improvement Areas in Oral Care. (October 2021) - Andersson, Maria; Persenius, Mona
Introduction: Oral care to older people in short-term care units is a complex and challenging everyday practice for nursing staff. Oral care research and knowledge about prerequisites and obstacles is extensive. However, there is a lack of knowledge about how nursing staff in short-term care units describe their satisfaction about provided oral care in order to maintain older people's oral health. Objective: The purpose of this study was to describe how nursing staff perceive their satisfaction of oral care provided for older people in short-term care units and to identify oral care improvements. Methods: This study reports on the results of two open-ended questions that were part of a larger study. Informants ( n = 54) were nursing staff working in the involved short-term care units in municipalities from both densely and sparsely populated regions in central and northern Sweden. The answers to the open-ended questions were analyzed using content analysis. Results: The analysis yielded one main category; " Working together to improve satisfaction with older people's oral care" and four subcategories: " Older people's oral health, " " Consideration and respect for the older person's autonomy, " " Having access to adequate products, " and " Working together in the same direction. " Conclusion: Identification of older people's oral health problems together with adequate nursing intervention will increase older people's health outcomes and quality of life. However, regardless of work role, the nursing staff might have difficulty changing their behavior or transforming intentions into actions. Oral care is a complicated and proactive practice that requires nursing staff's attention as well as both educational and organizational initiatives. Working in a supportive and collaborative relationship provides prerequisites for optimal oral care in short-term care units.